Cash Management Analysis in an Efforts to Maintain Liquidity Stability at PT Midi Utama Indonesia tbk 2020-2023 Period - Seleky, Roy; Christianty, Restia (ProBisnis : Jurnal Manajemen, 2025)
This study aims to analyze cash management in an effort to maintain liquidity stability at PT MIDI UTAMA INDONESIA Tbk for the period 202-2023.The type of research is quantitative descriptive research, using data sourced from IDKS as a research instrument. Data analysis techniques use Cash Management analysis (Optimal Cash Balance and Liquidity Ratios such as Current ratio, Quick ratio and cash ratio.The results of the study show that the company's ability has not been able to provide good results. This is proven by the calculation of the optimal cash balance that the company should have from 2020 - 2023 has never been achieved by the company, in terms of calculating the Liquidity ratio, all the ratios calculated show that the results obtained are at a figure > 1, which means that the company's cash has not been able to meet its obligations.